Somatic mosaicism in STAG2-associated cohesinopathies: Expansion of the genotypic and phenotypic spectrum - Schmidt, Julia; Dreha-Kulaczewski, Steffi; Zafeiriou, Maria-Patapia; Schreiber, Marie-Kristin; Wilken, Bernd; Funke, Rudolf; Neuhofer, Christiane M; Altmüller, Janine; Thiele, Holger; Nürnberg, Peter; Biskup, Saskia; Li, Yun; et al. (Frontiers in Cell and Developmental Biology, 2022)
STAG2 is a component of the large, evolutionarily highly conserved cohesin complex, which has been linked to various cellular processes like genome organization, DNA replication, gene expression, heterochromatin formation, sister chromatid cohesion, and DNA repair. A wide spectrum of germline variants in genes encoding subunits or regulators of the cohesin complex have previously been identified to cause distinct but phenotypically overlapping multisystem developmental disorders belonging to the group of cohesinopathies. Pathogenic variants in STAG2 have rarely been implicated in an X‐linked cohesinopathy associated with undergrowth, developmental delay, and dysmorphic features. Here, we describe for the first time a mosaic STAG2 variant in an individual with developmental delay, microcephaly, and hemihypotrophy of the right side. We characterized the grade of mosaicism by deep sequencing analysis on DNA extracted from EDTA blood, urine and buccal swabs. Furthermore, we report an additional female with a novel de novo splice variant in STAG2. Interestingly, both individuals show supernumerary nipples, a feature that has not been reported associated to STAG2 before. Remarkably, additional analysis of STAG2 transcripts in both individuals showed only wildtype transcripts, even after blockage of nonsense-mediated decay using puromycin in blood lymphocytes. As the phenotype of STAG2-associated cohesinopathies is dominated by global developmental delay, severe microcephaly, and brain abnormalities, we investigated the expression of STAG2 and other related components of the cohesin complex during Bioengineered Neuronal Organoids (BENOs) generation by RNA sequencing. Interestingly, we observed a prominent expression of STAG2, especially between culture days 0 and 15, indicating an essential function of STAG2 in early brain development. In summary, we expand the genotypic and phenotypic spectrum of STAG2-associated cohesinopathies and show that BENOs represent a promising model to gain further insights into the critical role of STAG2 in the complex process of nervous system development.